Palladium-catalyzed intramolecular diastereoselective dearomatization reaction of indoles with N-tosylhydrazones. Issue 20 (1st September 2021) - Duan, Shao-Bo; Zhang, Hong-Yu; Hao, Bo-Ya; Zhao, Jiquan; Han, Ya-Ping; Zhang, Yuecheng; Liang, Yong-Min
Abstract : A novel, highly diastereoselective palladium-catalyzed dearomative reaction of N -halobenzoyl o -haloaniline derivatives has been developed using functionalized N -tosylhydrazones as the coupling partners. Abstract : A novel, highly diastereoselective palladium-catalyzed dearomative reaction of N -halobenzoyl o -haloaniline derivatives has been developed using functionalized N -tosylhydrazones as the coupling partners. This cascade dearomative protocol, which proceeds through sequential dearomative carbopalladation, migratory insertion, and β-hydride elimination, provides a reliable and straightforward access to a wide range of structurally diverse tetracyclic indolines with C2-quaternary stereocenters in moderate to good yields and excellent diastereoselectivities with good functional group compatibility.